How the Incomplete Medicalization of Cannabis Shapes Patient Experiences. Issue 1 (2nd January 2023) - Reid, Matt
ABSTRACT: The medicalization of cannabis is currently described as incomplete in that it is not firmly under the control of biomedicine and because the medical definition coexists with other constructions of the plant, namely the recreational and criminal. This study examines how this incomplete medicalization is experienced by considering the sentiments expressed in five focus groups of cannabis patients (N = 21). Results indicate patients perceive both advantages and disadvantages to the incomplete medicalization of cannabis. Patients report that the current structure of state medical cannabis programs restores person control, allowing them to reduce their reliance on pharmaceuticals while driving them to learn more about their health and treatment options. Yet patients also report negative experiences with mainstream healthcare providers ranging from scorn to discrimination. Nonetheless, patients in this study desire that state-endorsed medical cannabis programs continue in a post-prohibition society because the advantages are interpreted as outweighing any disadvantages.